Civil Jurisdiction, Settler Politics, and the Colonial Constitution, circa 1840-58 - Ward, Damen (Victoria University of Wellington Law Review, 2008)
In early colonial politics, decisions about lower court jurisdiction often reflected competing ideas about the relationship between different parts and functions of government. In particular, court structure and jurisdiction could be seen as having important implications for the role and power of the governor. Appreciating the importance of jurisdiction as a way of defining, and arguing about, the distribution and exercise of political and legal authority in the colonial constitution allows connections to be drawn between different elements of settler politics in the 1840s and 1850s. The closing of the Court of Requests by Governor Grey in 1848, and the decisions of the Supreme Court judges in subsequent litigation, provide examples of this. Debate over the role of the governor in emerging systems of representative and responsible government after 1852 contributed to lower court jurisdiction remaining politically significant, particularly in relation to Māori. This is shown by considering parliamentary debates about the Stafford ministry's 1858 proposals for resident magistrates' jurisdiction over "native districts". The politics of jurisdiction were part of wider contests about the establishment and consolidation of particular political and institutional relationships within the colonial constitution. This multi-faceted construction of government authority suggests a need to reconsider elements of Pākehā colonial politics and law.